The Impact of Early Intervention on Motor Outcomes in Infants with Cerebral Palsy: A Longitudinal Study with Advanced Neuroimaging Correlates in Surabaya, Indonesia - Habiburrahman Said; Novalika Kurnia; Fatimah Mursyid; Sophia Lucille Rodriguez; Theresia Putri Sinaga; Aline Hafidzah (Sriwijaya Journal of Neurology, 2023)
Introduction: Cerebral palsy (CP) is a prevalent neurodevelopmental disorder affecting motor function in children. Early intervention (EI) has been shown to improve motor outcomes in infants with CP, but the underlying neural mechanisms remain poorly understood. This longitudinal study investigated the impact of EI on motor outcomes and its association with neuroimaging correlates in infants with CP in Surabaya, Indonesia. Methods: We recruited 60 infants diagnosed with CP aged 6-18 months in Surabaya, Indonesia. Participants were randomly assigned to either an EI group receiving 6 months of individualized, home-based intervention or a control group receiving standard care. Motor function was assessed using the Gross Motor Function Measure (GMFM-88) at baseline, 6 months, and 12 months. Advanced neuroimaging techniques, including diffusion tensor imaging (DTI) and functional magnetic resonance imaging (fMRI), were used to assess brain structure and function at baseline and 12 months. Results: Infants in the EI group demonstrated significantly greater improvements in GMFM-88 scores compared to the control group at 6 and 12 months (p < 0.05). DTI revealed increased fractional anisotropy (FA) in the corticospinal tract and corpus callosum in the EI group at 12 months, indicating improved white matter integrity. fMRI showed increased functional connectivity in motor networks in the EI group compared to the control group at 12 months. Conclusion: Early intervention significantly improved motor outcomes in infants with CP in Surabaya, Indonesia. These improvements were associated with enhanced white matter integrity and functional connectivity in motor-related brain regions. Our findings highlight the importance of early intervention in promoting neuroplasticity and improving motor function in infants with CP.